Species diversity of Arabis alpina L. communities in two Pb/Zn mining areas with different smelting history in Yunnan Province, China. (October 2019) - Li, Zuran; Colinet, Gilles; Zu, Yanqun; Wang, Jixiu; An, Lizhe; Li, Qing; Niu, Xiuyan
Abstract: In order to explore the species compositions and species diversity (Dominance (Do), Shannon-Wiener index (H′), Simpson diversity index (Dsi), Species richness (DMG ), Pielou evenness index (Epi) and Frequency (Fr)) of twenty Arabis alpina L. var. parviflora Franch communities, field investigation was conducted in Huize county, Yunnan province, China. Some 20 A. alpina communities were distributed in two traditional smelting tailing piles of Minbingyingjiying (TST) and Shangduoduo village (SDD) with different Pb smelting history. The morphological characteristics (plant height, branch number, basal leaf length, basal leaf width and root morphology) of A. alpina, contents and accumulation characteristics of eight potentially toxic metals (As, Cd, Cr, Cu, Pb, Zn, Al, Fe) in soil and plants were analyzed. The results showed that the morphological characteristics of A. alpina were mean plant height 12.25 cm, the basal leaf length 17.69 cm, leaf width 5.40 cm, the total root length 117.86 cm plant −1, the root diameter 0.90 mm. The leaves of A. alpina in SDD were longer and narrower with higher plant height compared with in TST. The main companion plants of A. alpina were Sporobolus fertilis (Steud.) W. D. Clayt, Arenaria orbiculata Royle ex Edgew. et Hook. F. and Eulalia speciosa . (Debeaux). The H′ and Dsi were 0.56–2.04 and 0.44–0.95, respectively. The plant species numbers, H', Dsi and Epi of A. alpina communities in TST were higher than those in SDD. Pb contents in shoot of two A. alpina samples were more than 1000 mg kg −1, Cd content in shoot of one A. alpina sample >100 mg kg −1 and Zn contents in shoot of seven A. alpina samples >10, 000 mg kg −1 with the enrichment factors and transport coefficients greater than 1. The results indicate that A. alpina as a Zn, Pb and Cd hyperaccumulator, could be used for long-term phytoremediation of soils contaminated by Cd, Pb and Zn. Species diversity of A. alpina community during long-term natural vegetation restoration was high in the middle succession with single-peak model, and A. alpina would be dominant in the succession climax stage in potentially toxic metal contamination areas. Highlights: Arabis alpina grown in mining area with long history showed greater space expansion capability. Arabis alpina is a Zn, Pb and Cd hyperaccumulator. Arabis alpina could be used for long-term phytoremediation of soils compound contaminated by Cd, Pb and Zn. Species diversity of A. alpina community was high in the middle succession.